OPTIMALISASI LETAK NOZZLE VENTURI MIXER PADA GENSET BERBAHAN BAKAR BIOGAS - Khudhori, Muhrom (Institut Teknologi Dirgantara Adisutjipto, 2013)
Carburetor modification to the venturi mixer to put a hole in the center of the venturi (end of hole venturi type nozzle on the outlet end venturi section) can turn the engine generator using biogas fuel. Airflow velocity carburetor venturi section will begin upon entering the venturi section and will be maximal at the time in the middle of the venturi section. So of course the location of the placement of venturi carburetor venturi mixer on the right cross section will be obtained velocity airflow + optimum biogas. It is necessary for optimizing the placement location of the modification of the carburetor venturi mixer, air flow + in order to obtain optimum biogas which will have implications for the performance of the generator engine. In this research, manufacture three prototypes nozzle venturi mixer that will be placed at different places in the venturi duct, then the performance test was done to determine the type and location of the venturi nozzle prototype mixer is optimal. From the results of this study that : 1) Prototype nozzle venturi mixer with the tip of the nozzle in the middle (shape elbow) has the most complicated construction than the second type (type 1 and 2) the other. Manufacturing and assembly to form the elbow (type 3) is also more complicated and more difficult , this is because the space available / remaining biogas is limited to hole channel, and 2) Using a prototype generator machine type 3 is more stable when compared with other types, despite the decline, but not very significant in comparison with the other 2 types, so the prototype mixer venturi nozzle is the most optimal type 3 (square shape).